ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEPUASAN PELANGGAN (Studi Pada Warnet Chamber, Semarang) - Erma Dwi Andriyani, 08.05.51.0083; Listiono, Djoko (Students Journal of Economic and Management, 2012)
This study aims to analyze the extent of the influence of service quality, price, and location of customer satisfaction. The population in this study is that all cafe customers Chamber Semarang. The number of samples is about 100 respondents. The data used in this study is the primary data using questionnaires. Analysis of the data which is used multiple linear regression analysis. Hypothesis testing using t test with the test results indicate that the quality of service, price, and location of positive and significant effect on customer satisfaction. Jointly testing using the F test showed that together the quality of product, price, and location have a significant effect on customer satisfaction. Coefficient of determination value of 0.768 or 76.8%. This means that the variable product quality, price and location have contributed as much as 76.8% of customer satisfaction. While the rest of 23.2% is affected by other variables not included in the study. Limitations of this study is the only study using a questionnaire as a data source does not use actual data, such as variable rates using the actual price. This study is limited by using avariable service quality, price, and location of the study should be conducted with a combination of other variables Key words: service quality, price, location, customer satisfaction.